2006
DOI: 10.1590/s1020-49892006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human immunodeficiency virus infection in patients with pulmonary tuberculosis at the National Chest Hospital in Jamaica

Abstract: The prevalence of HIV in patients with tuberculosis in Jamaica is similar to that in other developing countries, but the mortality rate is higher and this warrants prompt diagnosis of HIV infection and early institution of highly active antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Same findings but with lower rates were reported by Chum et al (13) in Tanzania, Kiwuwa et al in Uganda (l4) and Kuaban et al (15) in the Chest medicine tertiary hospital in_Yaounde-Cameroon. This was not the case in Jamaica where Akpaka et al (16) found that TB/HIV co-infection was more prevalent in males than females. This difference is probably due to the fact that in Africa, transmission of HIV infection is mainly heterosexual and women are more vulnerable whereas in Europe and the Americas, intravenous drug use and homosexual routes of transmission are the most common.…”
Section: Discussionmentioning
confidence: 92%
“…Same findings but with lower rates were reported by Chum et al (13) in Tanzania, Kiwuwa et al in Uganda (l4) and Kuaban et al (15) in the Chest medicine tertiary hospital in_Yaounde-Cameroon. This was not the case in Jamaica where Akpaka et al (16) found that TB/HIV co-infection was more prevalent in males than females. This difference is probably due to the fact that in Africa, transmission of HIV infection is mainly heterosexual and women are more vulnerable whereas in Europe and the Americas, intravenous drug use and homosexual routes of transmission are the most common.…”
Section: Discussionmentioning
confidence: 92%
“…Reports of similar studies in Nigeria found 12.0% in Ile-Ife [14], 10.0% in Kano [15], 10.5% and 14.9% among children and adults respectively in Sagamu [16,17], and 41.2% in Alushi [18]. Elsewhere, Akpaka et al [19] reported 11.6% TB and HIV co-infection in Jamaica. Also, 11.4% was found in Northwest Ethiopia [20], 55.5% in Western Kenya [9], 39.0% in Brazil [21] and 8.6% in India [22].…”
Section: Discussionmentioning
confidence: 95%
“…All patients had elevated ESR levels (Table 4). Among the patients with PTB co-infected with HIV, 54.17% of patient's CD4 count levels were more than 200 cells/mm 3 and 33.33% had in between 50 to 200 cells/mm 3 , whereas 12.5% had CD4 count less than 50 cells/cm 3 (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of HIV infection, clinical manifestations of TB are quite similar to that of HIV seronegative patients; however, at a later phase atypical features are common. 3 Most common symptoms of PTB are cough with expectoration and weight loss. Constitutional symptoms like fever, night sweats, generalised weakness, loss of appetite and other respiratory symptoms like chest pain, haemoptysis and breathlessness.…”
mentioning
confidence: 99%